2022
DOI: 10.1158/2159-8290.cd-20-1628
|View full text |Cite
|
Sign up to set email alerts
|

IL27 Signaling Serves as an Immunologic Checkpoint for Innate Cytotoxic Cells to Promote Hepatocellular Carcinoma

Abstract: Although inflammatory mechanisms driving hepatocellular carcinoma (HCC) have been proposed, the regulators of anticancer immunity in HCC remain poorly understood. We found that IL27 receptor (IL27R) signaling promotes HCC development in vivo. High IL27EBI3 cytokine or IL27RA expression correlated with poor prognosis for patients with HCC. Loss of IL27R suppressed HCC in vivo in two different models of hepatocarcinogenesis. Mechanistically, IL27R sig­naling within the tumor microenvironment restrains the cytoto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 111 publications
0
13
0
4
Order By: Relevance
“…Additionally, we found that the HDGF had a signi cant negative correlation with Cytotoxic and pDC in ltration in these tissues. These observations were signi cant as both cytotoxic and pDC cells are critical to both the antitumor response and [26,27] OS in HCC [28,29]. Interestingly however, the correlation between HDGF and Th2 cell in ltration was positive, suggesting that these cells may be linked to HCC progression potentially via their M2 macrophage recruitment and polarization as well as their immunosuppressive effects within the TIME [30].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the HDGF had a signi cant negative correlation with Cytotoxic and pDC in ltration in these tissues. These observations were signi cant as both cytotoxic and pDC cells are critical to both the antitumor response and [26,27] OS in HCC [28,29]. Interestingly however, the correlation between HDGF and Th2 cell in ltration was positive, suggesting that these cells may be linked to HCC progression potentially via their M2 macrophage recruitment and polarization as well as their immunosuppressive effects within the TIME [30].…”
Section: Discussionmentioning
confidence: 99%
“…Second, poor sleep quality can partly contribute to the alteration in serum levels of inflammatory markers, such as the accumulation of interleukin and tumor necrosis factor-α [23,24] . Interleukin-27 receptor (IL-27R) signaling was proven that it promoted liver cancer development in vivo [25] . Furthermore, prospective studies indicated that both too short and too long sleep duration were associated with a significantly high risk of type 2 diabetes [26] , which were also solid risk factors for liver cancer in patients with liver disease validated by both cohort and case-control study [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IL-27 might have a role as a predictive biomarker of immunotherapy for HCC. Turan Aghayev et al also reported that elevated IL27RA mRNA expression correlated with poor survival since the treatment in Korean, Chinese, and TCGA HCC cohorts [128].…”
Section: Cytokines and Chemokinesmentioning
confidence: 94%